THE SPIRITUAL FUNCTION OF THE TEACHER'S IMAGE IN A WORK OF ART (ON THE EXAMPLE OF THE NOVEL "GREEN NIGHT") - Sa’dullayeva Shahlo Anvarovna, (Research Focus International Scientific Journal, 2025)
this article discusses the coverage of social problems in the work of the Turkish writer Rashod Nuri Guntekin "Green Night", the author's attitude to the field of education. The work's protagonist, Teacher Şahin , talks about the ideological struggle he waged against those who misinterpreted religion and those who thought in two ways in the country. By analyzing the above, the spiritual importance of teachers in the revolutionary process during the newly emerging period of the Turkish Republic is revealed.